Right ventricular dysfunction during chemotherapy in patients with breast cancer - A. N. Sumin; Yu. S. Slepynina; А. V. Shcheglova; A. V. Ivanova; O. M. Polikutina (Кардиоваскулярная терапия и профилактика)
Aim. To assess the right ventricle (RV) during chemotherapy (CT) in patients with breast cancer (BC).Material and methods. The study included 40 women aged 35-72 years with BC who underwent anthracycline chemotherapy. The main group (n=40) included women with BC, examined at the first contact, 37 of whom were reexamined after 6 months. Control group (n=25) included women without BC.Results. In the main group, the median transverse dimension and anterior wall thickness of the RV were significantly greater than in the control group (p<0,001). Early diastolic transtricuspid flow velocity (Et) after 6 months was lower than in the control group (p=0,003). The ratio of Et to late (At) diastolic transtricuspid flow (Et/At) in BC patients significantly decreased during the follow-up period (p<0,05) when compared with the control group and baseline values. Higher values of Tei index were noted in the main group compared to the control one (p<0,05). Using logistic regression for the Tei index, the model included radiation therapy, the total anthracycline dose, and negative affectivity score as follows: F(3,17)=12,548, p<0,001, R2=0,729. For the Et/At ratio, additional radiation therapy and heart rate were significant factors as follows: F(2,16)=12,548, p=0,005, R2=0,526.Conclusion. Against the background of CT, deterioration of RV systolic (increase in Tei index and RV volume) and diastolic (decrease in Et and Et/At ratio) function was noted.